Factors affecting profitability of insurance companies in Bangladesh - Quazi Sagota Samina (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this study is to evaluate profit earning capacity of insurance companies in Bangladesh and to identify both company specific and macro-economic factors that influence the profitability. Design/methodology/approach: This study uses panel data collected on 21 insurance companies operating in Bangladesh over the period of 2017-2021. Ordinary Least Square (OLS) method of regression analysis has been applied in the study to identify the determinant variables of profit of insurance companies. Findings: The results show that volume of capital, proportion of investment and commission expense positively affect profitability of insurance companies whereas underwriting risk, tangibility, GDP and interest rate have neg-ative impact on profitability. Research limitations/implications: In a small economy like Bangladesh, the existence of a large number of in-surance companies creates a question of sustainability of these organizations. To sustain in the long run, the in-surance companies need to earn sufficient profit. This study focuses on the factors that may influence and enhance profit earning capacity of these organizations. The limitation of this study is that the sample includes both life and non-life insurance companies. Therefore, future studies can be done focusing each sector separately. Originality/value: There is no other study focusing on profitability of insurance companies in Bangladesh concen-trating recent scenario and large sample size. This research contributes the regulatory authority to direct insurance companies in the path of earning better profit. The findings of the study can also benefit the insurance companies as they can know the areas where they should focus more and take care of while operating business.
Keywords: 650; insurance; profitability; determinants; economic; Bangladesh